A CRITICAL ANALYSIS OF THE LAW OF GENOCIDE - Sehgal, Pranshu (Commonwealth Law Review Journal, 2017)
The Convention against Genocide, rose from the ashes of Holocaust. The ICTY and ICTR have been set up for a purpose which can be explained in two limbs as follows: a. To prevent genocide. b. To punish those committing the horrendous and monstrous act of genocide. Article 6 of the Rome Statute defines Genocide as: For the purpose of this Statute, "genocide" means any of the following acts committed with intent to destroy, in whole or in part, a national, ethnical, racial or religious group, as such: (a) Killing members of the group; (b) Causing serious bodily or mental harm to members of the group; (c) Deliberately inflicting on the group conditions of life calculated to bring about its physical destruction in whole or in part; (d) Imposing measures intended to prevent births within the group; (e) Forcibly transferring children of the group to another group. Under the above mentioned definition it is clear that the definition is an exclusive definition and only when any of the acts as mentioned from (a) to (e) is fulfilled can the act of genocide be said to be committed. The same is an unambiguous and a settled position in the law. The genocide offence has two separate mental elements, namely a general one that could be called ‘general intent’ or ‘intent to destroy’.1 The ‘intent to destroy’ constitutes an additional subjective requirement that complements the general intent and goes beyond the objective elements of the offence. 2 Further, genocide requires an ulterior intent (‘“surplus” of intent’3 ).